Sustainable cereal production through integrated crop management: a global review of current practices and future prospects - Yamini, Vaddula; Singh, Kulvir; Antar, Mohammed; El Sabagh, Ayman (Frontiers in Sustainable Food Systems, 2025)
Among cereals, three crops namely maize, wheat, and rice account for 90% of the total cereal production, with global production levels of 791.2, 522.6, and 1229.63 million tons for wheat, rice and maize, respectively. The global challenges of food insecurity, climate variability, and unsustainable land use necessitate a redefined approach to cereal production, focusing on climate resilience, low vulnerability, and high productivity while establishing food and environmental safety. Integrated crop management (ICM) offers a holistic farming approach that integrates various agricultural practices to ensure long-term benefits and mitigate risks. This comprehensive review examined a total of 108 documented studies from existing literature pertaining to the last 23 years, besides case studies on ICM in rice, wheat, and maize production, analyzing its benefits, challenges, and future directions. In Asian countries, where rice is a staple food, ICM practices have effectively addressed challenges such as yield stagnation, declining profits, and crop failures. Nutrient and pest management, along with conservation agriculture (CA), have played a crucial role in overcoming these challenges. China’s implementation of site-specific management duly integrated with other practices, has successfully reduced excessive nitrogen use besides improved environmental and health outcomes. Sustainable corn production has been achieved in the USA and Africa through comprehensive implementation of CA and crop diversification. Globally, ICM has demonstrated yield increases of 10–19% for rice, 16–30% for wheat, and 13.5–30% for maize crops. Despite having ample potential, the widespread adoption of ICM faces technical, climate-related, and economic constraints. Overcoming these challenges requires targeted training, extension services, and supportive policies. Furthermore, future research should focus on addressing key knowledge gaps to facilitate the widespread implementation of ICM. While promoting climatic resilience and sustainability in cereal production systems, ICM can contribute to food security and environmental preservation globally.